KARAKTER KEBANGSAAN - Aprillia Sumenda; Nomi Tampilang; Christo Rompis; Melky Pangemanan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
This research explores the important role of national character as the main foundation in forming identity and maintaining the integrity of the nation, especially in the era of globalization which expands intercultural interactions and the spread of foreign values. With the rapid flow of information from all over the world, maintaining a strong identity is crucial for every nation to overcome the challenges of an identity crisis that may arise. A qualitative approach was used in this research, by analyzing data from literature, interviews with experts, as well as policy studies in the fields of education and national culture. The results show that strengthening national character plays a role in preventing identity crises, increasing social unity, and protecting cultural integrity amidst the challenges of globalization. This research emphasizes the importance of sustainable national character education and policies that support the creation of a strong national identity.